Implementation of object oriented technology concept and rapid application development method in designing church service information system HKBP Perumnas Simalingkar - Sondang, Sondang (Jurnal Mandiri IT, 2024)
Designing information systems that are appropriate and in accordance with user needs is a key element of success in designing information systems that are fast, easy, and able to manage various data and information needed by users. In this context, Object Oriented Technology and the Rapid Application Development Method provide a powerful and easy approach to designing information systems. This article describes the stages of the Rapid Application Development method starting from planning, design, development, and implementation in designing information systems tailored to the needs of the HKBP Perumnas Simalingkar Church Service. In addition, this article also discusses the use of Codeigniter 4 which has adopted the concept of Object Oriented Technology to make it easier to create complex information systems. Then this article also discusses the use of the Unified Modeling Language as a tool to model the design of information systems. The combination of the Object Oriented Technology concept and the Rapid Application Development method can increase the acceleration of making information systems and produce powerful information systems.